Hiatal hernia repair and magnetic sphincter augmentation to treat laryngopharyngeal reflux aiding the prevention of recurrent laryngeal cancer. Issue 1 (2nd January 2021) - Smoot, Madeline; Ward, Marc A.; Arviso, Lindsey; Sanchez, Christine E.; Leeds, Steven G.
Abstract: Laryngopharyngeal reflux (LPR) is a difficult disease to treat and can result in mucosal injury in the pharynx and larynx. This typically results in symptoms such as cough, hoarseness, and globus sensation, but the manifestation of cancer is a possibility. We present a patient with a squamous cell cancer of the larynx who was diagnosed with gastroesophageal reflux disease (GERD) and found to have LPR. The cancer was treated locally and GERD was eradicated with magnetic sphincter augmentation. After 15 months of follow-up, there was no residual cancer. This case highlights the role that untreated LPR may play in patients' risk of developing laryngeal cancer.